Didactics to Enhance Observation, in Educational Contexts - Alfonso Corredor, Breed Yeet; González-Crespo, Rubén; Montenegro-Marin, Carlos Enrique; Sánchez Martelo, Carlos Augusto (Springer, 2024)
This research aims to enhance the development of observation skills as a basic process of formative research, due to the problems that undergraduate students have at the time of wanting to carry out essential observation processes in writing. of research articles or degree works. With them, the research is focused on the skills of identifying characteristics and description, through the qualitative approach and quantitative analysis and the methodology is the case study. The study group belongs to an undergraduate program in the face-to-face modality to which the following instruments were applied: an initial one, the designed didactics and a final one to verify the effectiveness of the didactics. The four phases of implementation of this research allowed knowing those preconceptions or previous knowledge with which the population had until the verification of the didactics. The first phase was constituted in the design of instruments, which corresponded to the following instruments: Initial, final, didactic design, self-diagnosis, field diary and process verification. Initial which identifies the level of observation of the population, final where a post-test is carried out, design of the didactics that would seek to potentiate the observation, self-diagnosis this instrument was designed and applied in the validation of the instruments, diary of field where the most relevant stories and events will be written down. The second phase consists of the validation of the instruments, which allowed them to be evaluated and adjusted. The third phase is the application of the instruments with the selected population. The fourth phase is the analysis of the results.
Keywords: didactics; observation skills; formative research; Scopus(2)